Clinical predictors of long-term survival in newly diagnosed transplant eligible multiple myeloma: an IMWG Research Project - Usmani, Saad Z.; Hoering, Antje; Cavo, Michele; Miguel, Jesus San; Goldschmidt, Hartmut; Hajek, Roman; Turesson, Ingemar; Lahuerta, Juan Jose; Attal, Michel; Barlogie, Bart; Lee, Jae Hoon; Kumar, Shaji; et al. (Blood cancer journal, 2018)
Purpose: multiple myeloma is considered an incurable hematologic cancer but a subset of patients can achieve long-term remissions and survival. The present study examines the clinical features of long-term survival as it correlates to depth of disease response. Patients & Methods: this was a multi-institutional, international, retrospective analysis of high-dose melphalan-autologous stem cell transplant (HDM-ASCT) eligible MM patients included in clinical trials. Clinical variable and survival data were collected from 7291 MM patients from Czech Republic, France, Germany, Italy, Korea, Spain, the Nordic Myeloma Study Group and the United States. Kaplan-Meier curves were used to assess progression-free survival (PFS) and overall survival (OS). Relative survival (RS) and statistical cure fractions (CF) were computed for all patients with available data. Results: achieving CR at 1 year was associated with superior PFS (median PFS 3.3 years vs. 2.6 years, p < 0.0001) as well as OS (median OS 8.5 years vs. 6.3 years, p < 0.0001). Clinical variables at diagnosis associated with 5-year survival and 10-year survival were compared with those associated with 2-year death. In multivariate analysis, age over 65 years (OR 1.87, p = 0.002), IgA Isotype (OR 1.53, p = 0.004), low albumin < 3.5 g/dL (OR = 1.36, p = 0.023), elevated beta 2 microglobulin ≥ 3.5 mg/dL (OR 1.86, p < 0.001), serum creatinine levels ≥ 2 mg/dL (OR 1.77, p = 0.005), hemoglobin levels < 10 g/dL (OR 1.55, p = 0.003), and platelet count < 150k/μL (OR 2.26, p < 0.001) appeared to be negatively associated with 10-year survival. The relative survival for the cohort was ~0.9, and the statistical cure fraction was 14.3%. Conclusions: these data identify CR as an important predictor of long-term survival for HDM-ASCT eligible MM patients. They also identify clinical variables reflective of higher disease burden as poor prognostic markers for long-term survival.
Gesehen am 25.02.2020
Bei den Verfasserangaben ist Hartmut Goldschmidt geschrieben: Hartmut Goldschimdt